Re‐evaluation of sodium aluminium silicate (E 554) and potassium aluminium silicate (E 555) as food additives. (10th June 2020) - ,; Younes, Maged; Aquilina, Gabriele; Castle, Laurence; Engel, Karl‐Heinz; Fowler, Paul; Frutos Fernandez, Maria Jose; Fürst, Peter; Gürtler, Rainer; Gundert‐Remy, Ursula; Husøy, Trine; Manco, Melania; et al.
Abstract: The Panel on Food Additives and Flavourings (FAF) provided a scientific opinion re‐evaluating the safety of Sodium aluminium silicate (E 554) and potassium aluminium silicate (E 555) as food additives. The Scientific Committee for Food (SCF) assigned these food additives together with other aluminium‐containing food additives a provisional tolerable weekly intake (PTWI) of 7 mg aluminium/kg body weight (bw). In 2008, EFSA established a tolerable weekly intake (TWI) of 1 mg aluminium/kg bw per week. Sodium aluminium silicate was shown in rats to be absorbed to a limited extent at 0.12 ± 0.011%. The Panel considered that potassium aluminium silicate would be absorbed and become systemically available similarly to sodium aluminium silicate. No information on the physicochemical characterisation of sodium aluminium silicate and potassium aluminium silicate when used as food additives has been submitted and only very limited toxicological data were available for sodium aluminium silicate. Exposure to E 554 was calculated based on the reported use levels in food supplements. Exposure to aluminium from this use of E 554 was calculated to exceed the TWI for aluminium. Based on the data provided by interested business operators, the Panel considered that E 555 is not being used as a carrier, but as an inseparable component of 'potassium aluminium silicate‐based pearlescent pigments'. The Panel calculated the regulatory maximum exposure to E 555 as a carrier for titanium dioxide (E 171) and iron oxides and hydroxides (E 172). Exposure to aluminium from this single use at the maximum permitted level could theoretically far exceed the TWI. Considering that only very limited toxicological data and insufficient information on the physicochemical characterisation of both food additives were available, the Panel concluded that the safety of sodium aluminium silicate (E 554) and potassium aluminium silicate (E 555) could not be assessed.